Generalist case management : - Woodside, Marianne (Brooks/Cole, Cengage Learning, 2013)
Realistic and relevant, this counseling book provides you with the fundamental skills and information you need to coordinate and provide services to a variety of populations. Case studies, interviews with human service case managers nationwide, and opportunities to apply what you learn to real-life issues are just a few of the tools that will help you become an effective advocate for your client. Available with InfoTrac Student Collections http://gocengage.com/infotrac.